Optimization on alkaline and enzymatic extraction of tea flower protein and its functional properties - HOU Ling; SHEN Xian; CHEN Lin; KIM Eunhye; WU Yuanyuan; TU Youying (浙江大学学报. 农业与生命科学版)
Tea flower is a new food resource with high protein and low fat, but there are few reports on the total protein extraction of tea flower so far.In this work, the tea flower protein was classified by Osboren method, and alkaline and enzymatic extractions were used for obtaining the total protein of the tea flower, and the functional properties of the protein were further analyzed. The single factor design of alkaline extraction was four levels of NaOH concentration (0.01, 0.05, 0.10 and 0.30 mol/L), five levels of time (0.5, 1.0, 2.0, 3.0 and 4.0 h), four levels of temperature (40, 60, 80 and 90 ℃) and five levels of liquid-solid ratio (8∶1, 15∶1, 20∶1, 30∶1 and 60∶1). Screening test result showed that the alkaline protease was the most suitable enzyme for enzymatic extraction, and the single factor design of enzymatic extraction was four levels of the amount of alkaline protease (0.1%, 1.0%, 4.0% and 8.0%), four levels of liquid-solid ratio (10∶1, 20∶1, 30∶1 and 40∶1), four levels of time (0.5, 1.0, 2.0 and 3.0 h) and three levels of temperature (30, 50 and 70 ℃).The results of Osboren experiment showed that the tea flower proteins were mainly composed of albumin, accounting for 53.86%, which was suitable for alkaline extraction. Based on the results of single factor test and orthogonal array design, the optimal conditions of alkaline extraction were 0.15 mol/L NaOH, 2.5 h, 75℃ and liquid-solid ratio of 30∶1, and the highest protein extraction rate and purity were 91.45% and 90%, respectively. The optimal condition of enzymatic extraction were 5% alkaline protease, liquid-solid ratio of 50∶1, 2 h and 60 ℃, and the highest protein extraction rate and purity were 79.12% and 55%, respectively.The functional properties of the tea flower protein from alkaline and enzymatic extractions were different. The purity, water retention capacity, emulsion stability and foamability from alkaline extraction were 90%, 4.00 mL/g, 85.18% and 100.00%, which were higher than those (55%, 3.60 mL/g, 30.76% and 80.00%) of enzymatic extraction. The emulsibility, oil absorption capacity, foam stability and solubility of the tea flower protein from enzymatic extraction were 83.87%, 4.40 mL/g, 72.92% and 89.00%, which were higher than those (77.14%, 4.00 mL/g, 40.00% and 60.60%) of alkaline extraction. Besides, the protein from alkaline and enzymatic extractions had good abilities on scavenging 1, 1-dipheny-2-picryhydrazyl (DPPH) free radical with the rate of 50.79% and 56.04% respectively, suggesting ant-i oxidative function of the tea flower protein.In sum, the present work provides optimization methods on the extraction of tea flower protein. The good functional properties with water retention capacity, oil absorption capacity, emulsibility, foamability and ant-i oxidative ability and so on of the protein will expand the application of tea flower in the field of food and cosmetics.